SILSILAH YESUS MENURUT INJIL MATIUS - Samuel Benyamin Hakh (Litbang STFT Widya Sasana Malang, 2009)
Genalogy is usely be used as a tools in order to trace identity of some one, so that he or she can get an acknowledgment in the society. Because without the acknowledgment, the person can not be received in relation with others. When Matthew’s community face with crisis identity because they were rejected by Jews community, Matthew formed the genealogy of Jesus to declare their identity. The crisis identity was emerged because of their faith in Jesus as the Lord, and their Saviour. But, like the Jews community, they perform the Abraham tradition as well. Therefore, Matthew made up this genealogy to connect their tradition into the faith tradition of Abraham. The aim was to explain that Jesus, the son of Daud and Abraham, to whom they believed, was the heir of the salvation which be promised by God. Therefore, everyone who believes in Him, they get the salvation and grace of Abraham.